Effect of Bushen Yutai Recipe on IVF Patients Subjected to Mild Ovarian Stimulation - Jiang, Xiaomei; Yan, Hua; Zhong, Xiufang; Tong, Guoqing; Zhang, Wuwen (Frontiers in Medicine, 2020)
The Traditional Chinese Medicine herbal recipe,-Bushen Yutai,the article investigated the effects in IVF Patients subjected to Mild Ovarian Stimulation. 219 infertile patients were randomly divided into 2 groups- the control group and herbal treatment group. By studying, we found oestrogen levels (E2) on the HCG triggering day was significantly lower in the control group (p<0.05); with positive blood flow being less detected by ultrasound scanning on both the day of HCG triggering and day of fresh embryo transfer for the control group (P<0.05). Additionally, the blood flow index, retroactive and proactive inhibition (PI and RI), was higher in the control group; while the fertilization rate and number of high quality embryos in the control group were lower than the control TCM experimental group (p< 0.01). The expression levels of the endometrial receptivity gene, VEGF, was lower in the control group versus the TCM experimental group on the day of fresh embryo transfer (p<0.05); while the rate of fresh embryo transfer in the control group was lower than the TCM experimental group (p<0.05). In conclusion, the TCM could increase the E2 during the IVF stage, with a higher number of oocyte and higher quality embryos. It also improved the Improving the endometrium and increased the level of VEGF gene expression. By enhancing the fresh embryo transfer rate in a minimal ovarian stimulation protocol, and by improving the clinical pregnancy and ongoing pregnancy rates, the Bushen Yutai recipe could be able to increase fresh embryo transfer and higher quality embryos.